THE POTENTIAL EFFECT OF L-CARNITINE AND EXERCISE ON MUSCLE STRENGTH IN AGING: A LITERATURE REVIEW - Kusuma Sri Whisnu Puteri; Kristina Puspadewi; Indira Vidiari Juhanna; I Putu Adiartha Griadhi (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2023)
Aging is an inevitable process, and it can affect various aspects of the human body, including the musculoskeletal system. L-carnitine (LC) has the potential to be used in conjunction with exercise to mitigate the loss of muscle strength associated with aging. This review aims to investigate the impact of LC and exercise on muscle strength in the context of aging. We conducted a comprehensive literature search using various online databases such as PubMed, EMBASE, CENTRAL, and Google Scholar. Our search involved keywords such as